Impact in the integral health of the workers the area technology of the information who make home office during Covid -19 - Pena Téllez, Maria Elizabeth (2021)
Introduction: With the social isolation imposed by the Covid 19 pandemic, teleworking in the home office modality has been an alternative used by some companies. Objective: To determine the impact of this remote work on the integral health of workers. Methodology: A cross-sectional study was carried out, through the "Google Forms" platform, a semi-structured questionnaire was elaborated that was sent to 150 information technology workers from a medium-sized municipality in the state of São Paulo, to obtain information on the variables: age, sex, working conditions, oral and systemic health, oral hygiene habits, musculoskeletal pain, physical exercises and emotional state. Results: Of the total of 116 responses received, 87.07% belonged to the male sex, 100% reported concern with their oral and general health, 56.03% reported changes in their eating habits, 44.83% increased food consumption and 77.58% reported feeling concerned and anxious. The prevalence of painful musculoskeletal symptomatology manifested in 100% of workers predominantly found in the cervical region (53.44%). In general, low frequency of physical activity and inadequate conditions for home work performance were corroborated. Conclusions: The change from the usual work routine to the home office modality (teleworking) significantly impacted the health of information technology workers. Given the possibility of maintaining this modality of remote work to reduce the exposure and spread of the virus, it is necessary to adopt strategies to preserve the integral health of these professionals.